The Effect of Yoga Exercise With Friction On The Application Of Transcutaneus Electrical Nerve Stimulation (TENS) On Pain Reduction In Low Back Pain Miogenic Patients - Hasbiah Hasbiah; Rachmaniar Rachmaniar; Muh Thahir; Aco Tang (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Low Back Pain is a complaint that is often encountered in everyday life. It is estimated that almost everyone has experienced back pain during their lifetime. Low Back Pain can be overcome by using Yoga, Transcutaneus Electrical Nerve Stimulation and TENS. This study aims to determine the effect of yoga exercise with Transcutaneus Electrical Nerve Stimulation on the application of Transcutaneous Electrical Nerve Stimulation (TENS) to reduce pain in myogenic Low Back Pain patients at the Maniangpajo Health Center, Wajo Regency. This study includes a quasi-experimental design with a pretest-post test two group design. The population in this study were 14 myogenic Low Back Pain patients aged 25-60 years, male and female, experiencing Low Back Pain due to muscle spasm at the Maniangpajo Health Center, Wajo Regency. The sample in this study were 14 people. The results showed that there was no difference in the effect between the 2 treatment groups on reducing pain in myogenic Low Back Pain patients at the Maniangpajo Health Center, Wajo Regency.Keywords: yoga; Transcutaneus Electrical Nerve Stimulation; TENS; Low Back Pain